2019
DOI: 10.3390/cells8050392
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Gene Therapy: Polarizing Therapeutic Goals for Treatment of Various Diseases

Abstract: Modulation of telomerase maintenance by gene therapy must meet two polarizing requirements to achieve different therapeutic outcomes: Anti-aging/regenerative applications require upregulation, while anticancer applications necessitate suppression of various genes integral to telomere maintenance (e.g., telomerase, telomerase RNA components, and shelterin complex). Patients suffering from aging-associated illnesses often exhibit telomere attrition, which promotes chromosomal instability and cellular senescence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…To fit the packaging by AAV, saCas9 [43] or other small size gene editing nucleases are to be used. To achieve tumor-specific gene expression, the TERT promoter, pending future modifications to improve its specificity and efficacy, may be a good choice [44]. The Cas9-based cancer therapy may further benefit from its multiplex targeting capacity, which enables simultaneous targeting multiple genes, for example telomerase genes (e.g., TERT), the ALT pathway genes, and other key ones to cancer cell survival pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To fit the packaging by AAV, saCas9 [43] or other small size gene editing nucleases are to be used. To achieve tumor-specific gene expression, the TERT promoter, pending future modifications to improve its specificity and efficacy, may be a good choice [44]. The Cas9-based cancer therapy may further benefit from its multiplex targeting capacity, which enables simultaneous targeting multiple genes, for example telomerase genes (e.g., TERT), the ALT pathway genes, and other key ones to cancer cell survival pathways.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, telomerase-targeted therapies may be associated with a risk of malignancy because overexpression of telomerase promotes cancer cell formation and growth. 63,64 Therefore, basic research, longitudinal studies, and well-designed clinical trials are imperative to expand our understanding of the molecular mechanisms underlying the association of hypertension with telomere length and telomerase activity. This could help to reduce the incidence of hypertension and assist in preventing hypertensive complications, further improving the quality of life of patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly believed that progressive attrition of TL could trigger the DNA damage response and disturb genomic integrity. [8][9][10] Although it is assumed that aberrantly short TL could drive genomic instability in hematopoietic stem cells and lead to further progression to AML, 24,25 little direct evidence has demonstrated that short TL is related to progression and the unfavorable survival of patients with AML. This is partly because most previous studies focused on exploring the correlation between TL and prognosis in whole cohorts of patients and consider less the impact of cytogenetic and molecular abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…evidence has shown that telomeres play a significant role in maintaining genomic and cytogenetic stability of human somatic cells. [8][9][10] Cells with aberrant, short telomeres may acquire chromosomal instability via chromosome end-end fusion. This can result in oncogenic transformation, which is a hallmark of many tumor types, including myelodysplastic syndromes (MDS) and AML.…”
mentioning
confidence: 99%